Nilai-Nilai Sosial Adat Minangkabau Dalam Silek Pauh Di Perguruan Singo Barantai Lubuk Lintah Kecamatan Kuranji Padang - Meri Rhama Nelly; Nerosti Nerosti (FBS Universitas Negeri Padang, 2020)
This study aims to reveal Minangkabau Custom Social Values in Silek Pauhat Perguruan Singo Barantai, Lubuk Lintah, Kuranji Padang. This is a qualitative research using descriptive analytical method. The main instrument used was the researcher itself and was assisted by supporting instruments such as writing instruments, cameras, and cellphones. The data used were primary and secondary data. The data were collected through literature study, observation, interview, and documentation. The data analysis was done byreducing the data, displaying the data, and making conclusion. Based on the results of this research, it is found that there are social values which can shape characters of the next generation, especially for sasian generation in Perguruan Singo Barantai. The Minangkabau social values found in Silek Pauh at Perguruan Singo Barantai, Lubuk Lintah, Kuranji, Padang, can be described as follows: 1) The social values of the step moves is a person can consider other people / be considerate of being Minangkabau people. 2) The social values of attack motion is a person has an accurate consideration in making decisions. 3) The social values of the lockdown moves is a person can adapt to any situation. 4) The social values of defend movesis a person has alertness and capabiltyin reading situations.